Binge Drinking in Spanish University Students: Associated Factors and Repercussions: A Preliminary Study - Herrero-Montes, Manuel (Int J Environ Res Public Health, 2019)
Alcohol consumption is common among young people. We performed a preliminary cross-sectional study among students (aged 18–30 years) enrolled for the academic year 2018–2019 at the Faculty of Nursing, University of Cantabria (Spain). We collected information on psychological and sociographic factors, tobacco and cannabis uses, and levels of physical activity by AUDIT questionnaires and in person interviews. The aim of our study was to assess the potential of binge drinking (BD) to adversely affect memory and executive function. We recruited 103 students, of whom 85% were female. The alcohol use pattern of slightly more than one-half of the total population was classified as BD. Among BD students, one-fourth were smokers, and nearly one-third had tried cannabis. The mean onset for alcohol use was 15.11 years. Despite our relatively small sample size, our results show that there are strong relationships between BD and both smoking and cannabis use.